A Novel Quality Evaluation Using a Smart Unique Language of Interaction Data Between Industry 5.0 and Society 5.0 - Baskar, Chinappan; Elim, Hendry (Pattimura Excellence Journal of Language and Culture, 2023)
A newly proposed technique is presented in order to evaluate the quality content of an open access paper in international open access journals. The method was carried out with a unique smart language of interacting data between Industry 5.0 and Society 5.0 online system via the insert of the following three numbers of Viewers, Likes, and Commends, respectively. Unlike h index that involved numbers of citations, this novel manner may open a new way to a wide insight in detecting the quality content of an open access paper worldwide. According to the tests of two different data extracted from Prof. Elim’s articles published in Kompasiana platform Blog, the quality analysis for each paper is reasonable and touching the core level of each investigated article. We therefore suggest that this piece of research work can be applied to study many other open access articles in different journals.